Differentiating embryonic stem cells: GAPDH, but neither HPRT nor beta-tubulin is suitable as an internal standard for measuring RNA levels. - Murphy, C; Polak, J (2002)
Embryonic stem (ES) cells are pluripotent cell lines that possess virtually unlimited self-renewal and differentiation capacity. Such characteristics make them potentially an invaluable cell source for diverse tissue-engineering applications. In vitro ES cell differentiation occurs spontaneously in three-dimensional structures termed "embryoid bodies" that mimic postimplantation embryonic tissue. HPRT, beta-tubulin, and GAPDH are commonly used as internal RNA standards in ES cell-derived gene transcription studies so that corrected sample mRNA levels can be obtained for (semi) quantitative gene expression data. However, if reliable data is to be obtained, it is essential that such housekeeping gene expression remains constant, and this has not been demonstrated for differentiating ES cell cultures, which represent a mixed and changing population of cells with time in culture. Therefore, in the present study, we tested the suitability of these housekeeping genes to act as true internal standards for differentiating murine ES cells cultured as embryoid bodies. PCR-amplified gene-specific products were quantified from digital images of ethidium bromide-stained gels using a computer software package. Both HPRT and beta-tubulin mRNA levels varied markedly in spontaneously differentiating and growth factor-supplemented (TGF-beta) ES cell cultures (p < 0.001, ANOVA), while GAPDH expression remained relatively constant (p > 0.2). Our results demonstrate the importance of fully validating housekeeping gene expression in in vitro ES cell gene transcription studies and suggest that GAPDH may be a suitable candidate to act as an internal RNA standard, while both HPRT and beta-tubulin appear to be inappropriate. Finally, we demonstrate enhanced mesodermal differentiation of ES cell-derived cultures by treatment with TGF-beta through significant upregulation of Brachyury T expression, with a concomitant decrease in expression of the undifferentiated ES cell marker Oct-4.